IMPLIKASI PERUBAHAN UNDANG-UNDANG KEOLAHRAGAANTERHADAP KECAKAPAN SUPORTER SEBAGAI SUBJEK HUKUM DALAMPEMBUATAN PERJANJIA - I Ketut Satria Wiradharma Sumertajaya; Ni Putu Ari Setyaningsih (Universitas Mahendradatta, 2023)
The aim of this paper is to analyze the implications of changes to the Sports Law on the proficiency of supporters as legal subjects in making agreements. This study uses a normative legal method because the focus of the study departs from the ambiguity of norms. The approaches used are Statute Approach and Conceptual Approach. The results of the study show that after the amendment, the Sports Law provides substantial benefits to the organizers of sports championships, one of which is regarding the arrangements concerning supporters in the Sports Law. The existence of supporters in the organizers of sports championships is obliged to register as a member of a sports supporter organizations or legal entities. Supporters have the ability as legal subjects in making agreements if the supporters are established in the form of a legal entity. If the supporters are established in the form of an organization, their ability to make agreements is determined based on the form of the organization at the time of establishment